Impuestos diferidos y su tratamiento contable y tributario, tras la valuación de inventarios bajo Niif. - Salinas Armijos, Karla Jazmin (My University, 2020)
The taxes are considered of great importance in the world, because of these they obtain the greater part of income in a country, so that later the state can use them in the solvency of expenses, investments or necessities that the inhabitants of the nation possess. With globalization and the need to negotiate with other countries in the world. Ecuador has been implementing the International Financial Reporting Standards (IFRS) by order of the Superintendence of Companies and Insurance since 2008 with the purpose of keeping a fair accounting in the country, where a statement of financial situation can be interpreted and understood in any other part of the world. It must also take into account tax effects that occur in the application of deferred taxes. The present investigative work deals of the tax effects that arise with the application of the IFRS, of which the taxable base is taken from the accounting records, as is the case of the Income Tax (IT). For the compliance with both of the accounting and tax regulations, the so-called Deferred Taxes are applied, with the analysis, accounting treatment and its accounting records in the development of a practical case raised, for this purpose, first the IFRS were analyzed as International Accounting Standards (IAS) 12 Deferred Taxes, IAS 2 Inventories, as well as the Organic Law of the Internal Tax Regime (OLITR) and other scientific articles or books referring to the subject to be treated.
Los impuestos se consideran de gran importancia en el mundo, debido a que de estos se obtiene la mayor parte de ingresos en un país, para que posteriormente el estado pueda utilizarlos en la solvencia de gastos, inversiones o necesidades que posean los habitantes de la nación. Con la globalización y la necesidad de negociación con otros países del mundo. Ecuador implementa las Normas Internacionales de Información Financiera (NIIF) por disposición de la Superintendencia de Compañías y Seguros desde el año 2008 con la finalidad de llevar una contabilidad ecuánime en el país, donde pueda ser interpretado y entendido un Estado de situación Financiera en cualquier otra parte del mundo. También debe tomar en cuenta efectos tributarios que se da en la aplicación de los impuestos diferidos. El presente trabajo investigativo trata de los efectos tributarios que se presentan con la aplicación de las NIIF, de los que la base imponible se toma desde los registros contables, como es el caso del Impuesto a la Renta (IR). Para el cumplimiento tanto de la normativa contable como tributaria se aplican los denominados Impuestos Diferidos, con el análisis, tratamiento contable y sus registros contables en el desarrollo de un caso práctico planteado, para esto primero se analizó las NIIF como son Normas Internacionales de Contabilidad (NIC) 12 Impuestos Diferidos, NIC 2 Inventarios, así como la Ley Orgánica de Régimen Tributario Interno (LORTI) y demás artículos científicos o libros referentes al tema a tratar.
Keywords: NORMAS INTERNACIONALES DE INFORMACIÓN FINANCIERA (NIIF); IMPUESTO A LA RENTA (IR); IMPUESTOS DIFERIDOS; INVENTARIOS